Med literaturo in novomedijsko umetnostjo - Vaupotič, Aleš (Primerjalna književnost, 2013)
The paper examines whether literariness is part of a "new media object" (Manovich). An example of new media art is websites that generate sonnet-like texts, which poses the question of a possible new media sonnet or, in more general terms, new media poetry in general. The projects by Vuk Ćosić and Teo Spiller are cases of new media textuality constructed from the relationship between authors' control over textual elements on the one hand, and user's intervention into an open text on the other.
Keywords: Ćosić, Vuk, 1966-; Spiller, Teo, 1965-; digitalna književnost; spletna poezija; soneti; kibertekstualnost; novi mediji; literarnost